Cardiac Magnetic Resonance: A Multi-Parametric Imaging to Guide Management in Chronic Ischemic Heart Failure - Novi Anggriyani (The Indonesian Heart Association, 2017)
Chronic heart failure is a major public-health problem with a high prevalence, high mortality and complex treatment. A comprehensive analysis is needed to provide optimal therapy to these patients. Non-invasive imaging plays a central part by offering a complete approach in patients with ischemic heart disease (IHD). Cardiac magnetic resonance imaging (CMR) has emerged as an established advanced multi-parametric imaging modality for the functional and anatomical assessment of cardiovascular disease. This review describes the practical aspects of CMR imaging, and then discusses the role of CMR in the diagnosis and management of chronic IHD, its infarct related complications, such as secondary mitral regurgitation, left ventricular (LV) thrombus, and ventricular tachycardia (VT).